Control of Occupational Safety and Health Risk Using the Hirarc Method (Case Study : PT Sari Warna Asli V Kudus) - Hafidh Munawir; Nugraeni Dwi Hapsari (Procedia of Engineering and Life Science, 2021)
PT Sari Warna Asli V is a yarn spinning manufacturing company. Based on the company's work accident record, in 2019 in the production department there were 19 work accidents and in 2020 as many as 18 work accidents. Total work accidents in 2019 were 14 cases that occurred in Spinning Mills I and 5 cases in Spinning Mills II. Meanwhile, in 2020, 12 cases occurred in Spinning Mills I and 6 cases in Spinning Mills II. The purpose of this research is to identify the potential hazards that exist, assess the risks that may occur at each work station in Spinning Mills I, so that risk control can be given so that the company can avoid any possible harm. The method used is Hazard Identification Risk Assessment Risk Control (HIRARC). Research data collection was obtained from observations at Spinning Mills I, interviews, documentation, and literature studies. The results of the study at 6 work stations on repair and maintenance activities obtained the percentage of potential hazards of 61% (49 risks) are low risk (low risk), 13% (10 risks) are moderate risk (moderate risk), 26% (21 risks) are high risk (high risk), and there are not potential work hazards with very high category (extreme risk). Risks included in the high risk category are falling from above when clearing blockages, broken hands/fingers exposed to rotating machines, fire, hearing loss, and fatigue. Risk control that can be done by the company includes adding SOPs, safety signs, and safety talk, K3 training to increase worker knowledge, providing PPE that must be used according to standards, installing automatic sensors that can detect approaching hands, providing safe distance limits/floor markings. production and routine cleaning.